THE REILLY’S INTEGRAL FORMULA ON SEMI-RIEMANNIAN MANIFOLDS WITH NONDEGENERATE BOUNDARY - Mahmut Ergüt; Mihriban Külahcı (Boletim da Sociedade Paranaense de Matemática, 2013)
In this paper, we obtained the Reillys integral formula on semi-Riemannian manifolds with nondegenerate boundary.